Natural radioactivity in marine sediment of Khor- Abdulla Northern west of the Arabian Gulf - Subber, Abdul; Jaber, Munaf Qasim; Al-Hashmi, Noori H.N. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
This work presents measurements of natural radionuclides (238U, 226Ra, 232Th and 40K) in the sea sediment using gamma spectroscopy. The sediment samples were collected from coastal and deep water using special equipment for this purpose. This work was performed in Khor-Abdulla, northern west of the Arabian Gulf to establish the baseline data level for naturally occurring radionuclides in the study area and will be useful for tracking and assessing any accentual pollution in the marine environment in the region. The average values of 232Th, 238U,226Ra, 40K are 5.6 Bq/kg, 7.2 Bq/kg, 44.4 Bq/kg and 293.9 Bq/kg respectively. It is found that,the mean radium equivalent Raeq and effective dose rates are 84.5 Bq/kg and 0.046 mSv/y respectively and they are well below the recommended limit of international committees.